Assessment of Environmental Control Policy Elements’ Somersaults in Ilupeju - Ekiti, Ekiti State, Nigeria - Adejumo, Aderinola A.; Kupolati, Deborah Taiwo; Aregbesola, Foluso Bolanle; Muhammad, Sa'adah Ayeni; Aderinola, Adeola Deborah; Obajaja, Caleb Ofumi; Madu, Francis Ugochukwu; Otugboyega, Joseph Olusoji; Ayo, Itunu Oluwatosin; Salami, Kaseem Dele (Journal of Science Research and Reviews, 2025)
Environmental policy elements are crucial for safeguarding natural resources, reducing pollution, and promoting sustainable development in Nigeria, particularly in Ilupeju Ekiti, Ekiti State. Despite national frameworks like the National Environmental Standards and Regulations Enforcement Agency (NESREA) Act and state-level statutes, environmental degradation persists. A study assessed the existing Environmental Control Policy Elements (ECPE), implementation extent, strategies, and factors influencing ECPE in the area. Researchers surveyed 124 stakeholders, including farmers, traders, artisans, teachers, commercial drivers, and students, using simple random sampling. Results showed that respondents, mostly females (50.8%) with tertiary education (57.5%), were aware of ECPE guiding environmental use (83.3%) and enacted laws (71.7%). However, 73.3% rated implementation strategies as ineffective, and 99.2% were unaware of specific government strategies. Political factors (70.8%) were major contributors to ECPE somersaults, with negative impacts on waste management (65.0%) and overall environmental quality. Logit regression analysis revealed that age (-4.09), educational status (0.000), and awareness of policy enforcement agencies (0.256) influenced ECPE implementation. The study confirms robust ECPE existence but highlights ineffective implementation and enforcement. The study concludes that prohibition laws are a step in the right direction, and recommends government support for enforcement agencies to ensure effective compliance monitoring and ECPE implementation.
Keywords: Policy elements; Environmental control; Policy implementation; Policy somersault; Policy strategies